Leadership Style as a Determinat of Employee Performance in Hospitality Industry: A Case Study at SS Hotel in Legian Bali - Anak Agung Made Restu Adi Wiguna; Ni Desak Made Santi Diwyarthi; Ida Ayu Kalpikawati (Journal of Economics, Management, Accounting and Computer Applications, 2026)
This study aims to examine the influence of leadership style on employee performance at The SS Hotel, Legian Bali. An appropriate leadership style plays a vital role in enhancing work motivation, loyalty, and employee productivity. The research employed a quantitative approach using a saturated sampling technique involving 152 respondents. Data were collected using a questionnaire with a five-point Likert scale. The results of a simple linear regression analysis indicate that leadership style significantly influences employee performance, with a coefficient of determination of 81.4%. These findings suggest that the majority of performance variation among employees can be explained by the leadership style applied. Therefore, improving leadership quality is a key strategy in supporting hotel management success.